2021
DOI: 10.3390/f12081010
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Water Supply and Evapotranspiration of Street Trees Using Hydro-Pedo-Transfer Functions (HPTFs)

Abstract: The climate, soil properties, groundwater depth, and surrounding settings in cities vary to a tremendous extent, which all lead to different growing conditions and health for street trees. Because of climate change, the availability of water in cities will undergo changes in the next decades. As urban trees have a very positive influence not only on microclimate but also on biodiversity and life quality in general, they need to be protected. Thus, we need to know how to measure and calculate the availability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
(49 reference statements)
0
12
0
Order By: Relevance
“…The model was parametrized for the most abundant tree species in Berlin, Tilia cordata (SenUVK, 2021), more specifically for a T. cordata with an age of 15–30 years, a crown size of 16 m 2 , a rooting depth of 1.5 m and a crop coefficient of KC = 1.4–1.6 (Wessolek & Kluge, 2021). The pheno‐multiplier ( cP = 0.5, for first 2 weeks of leaf development and last 2 weeks of leaf shedding) was added to describe the stage of development throughout the vegetation period.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The model was parametrized for the most abundant tree species in Berlin, Tilia cordata (SenUVK, 2021), more specifically for a T. cordata with an age of 15–30 years, a crown size of 16 m 2 , a rooting depth of 1.5 m and a crop coefficient of KC = 1.4–1.6 (Wessolek & Kluge, 2021). The pheno‐multiplier ( cP = 0.5, for first 2 weeks of leaf development and last 2 weeks of leaf shedding) was added to describe the stage of development throughout the vegetation period.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, existing water models for urban trees do not (Vico et al, 2014) or only partially include the effects of shading (Hörnschemeyer et al, 2021;Wessolek & Kluge, 2021). None of the studies considered varying shading patterns typically found within street canyons, which affect global radiation and potential evapotranspiration on a diurnal time scale.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations